Анатомічний стіл як найбільш технологічно вдала система візуалізації в медичній освіті - Мурзіна, Олена Анатоліївна; Грінівецька, Наталія Валеріївна; Вовченко, Михайло Борисович; Щербаков, Максим Степанович; Murzina, O. A.; Hrynivetska, N. V.; Vovchenk, M. B.; Shcherbakov, M. S. (My University, 2023)
У статті розглянуто переваги використання 3D анатомічного столу, такі як віртуальний маркер та текстові фрагменти, які можна використовувати під час заняття над зображенням тіла або органу з функцією збереження і закріплення. Використання медіатехнологій сприяє формуванню у студентів критичного мислення, більш ефективному засвоєнню навчального матеріалу та формує їх медіакомпетентність. Медіакомпетентність, зі свого боку, дає змогу формувати інформаційно насичене освітнє середовище, впливати на рівень медіакультури особистості, готувати її до безпечної і ефективної взаємодії із сучасним медіапростором. At the stage of preclinical professional training of future doctors of various specialties in institutions of higher medical education, the latest forms and methods of teaching students in the basic discipline “Human Anatomy” are used, therefore, the article considers various approaches to teaching this discipline. Thanks to the combination of classical approaches in the study of the basic discipline with innovative technologies such as digital library, digital textbooks, test systems, simulators, expert systems, anatomical table and 3D ORGANON is the basis for the formation of media competence of future doctors at the stage of pre-clinical professional training. The article discusses advantages of using a 3D anatomical table, such as a virtual marker and text fragments that can be used during a lesson on the image of a body or organ with the function of saving and fixing. An interactive technology of 3D anatomical table helps to avoid prior contact of an unprepared student with real biological material. While organizing the educational process, it is necessary to take into account the interactive features and creativity of students. Therefore, the use of media technologies in the educational process is one of the important and necessary ways to modernize higher medical education, taking into account the requests and needs of modern students. Therefore, future doctors use the 3D format device of the Anatomical Table and 3D ORGANON at the Zaporizhia State Medical and Pharmaceutical University while studying the “Human Anatomy” discipline. This provides an opportunity during the educational process to demonstrate the structure of organs and organ systems of the human body, which makes the lesson more informative and interesting. All this creates the impression of working with real objects, which contributes to a better understanding of the educational material, interests and motivates students to study human anatomy. The use of media technologies contributes to the formation of studentsʼ critical thinking, more effective assimilation of educational material and forms their media competence. Media competence, in turn, makes it possible to form an information-rich educational environment, to influence the level of media culture of an individual, to prepare him for safe and effective interaction with the modern media space.
Interactive anatomical table as the most technologically modern visualization system in medical education
Keywords: 3D анатомічний стіл; 3D ORGANON; новітні інноваційні методи навчання; медіа середовище; медіакомпетентність; 3D anatomical table; 3D ORGANON; the latest innovative teaching methods; media environment; media competence